From Meaningful to Meaningless Participation: The Tragedy of Indonesia’s Omnibus Law on Job Creation - Mochtar, Zainal Arifin; Arizona, Yance; Rahman, Faiz; Mubdi, Umar; Ruhpinesthi, Garuda Era; Wafi, Mochamad Adli (Jurnal Media Hukum, 2000)
Indonesia’s Constitutional Court introduced the concept of meaningful participation in the lawmaking process, emphasizing the right to be heard, considered, and explained. This concept was institutionalized through amendments to the Law on Lawmaking Procedures (Law Number 13 of 2022). However, meaningful participation remains poorly implemented, as demonstrated by the lack of public involvement in the issuance of the Government Regulation in Lieu of Law legalizing the Omnibus Law on Job Creation and the Constitutional Court's ruling on Law Number 6 of 2023 (Job Creation Law 2.0), which deemed public participation irrelevant for emergency laws. These developments highlight inconsistencies in applying the principle of meaningful participation in Indonesia’s legislative practices. This research evaluates the institutionalization of meaningful participation in Law Number 13 of 2022 and its practical application in Indonesia’s lawmaking process. This research uses doctrinal legal research methods by examining library materials and secondary data to analyze the legal framework and its implementation. The findings reveal a significant gap between the theoretical framework of meaningful participation and its application in practice, particularly in emergency lawmaking. In conclusion, while the institutionalization of meaningful participation reflects a positive step, inconsistent application undermines its potential to enhance democratic governance in Indonesia.